2021
DOI: 10.1108/jbim-07-2020-0371
|View full text |Cite
|
Sign up to set email alerts
|

Network interactions for pharmaceutical market access: findings from an explorative research

Abstract: Purpose The purpose of this paper is to investigate pharmaceutical market access (MA) and the interaction between the pharmaceutical company and other business and non-business actors (NBAs) involved in the MA of ethical drugs, to identify the main categories of actors, their role for MA and the content of the interaction, adopting an industrial marketing approach. Design/methodology/approach A qualitative interpretivist approach is adopted, with interviews as the primary data collection method: 36 interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Organizations in highly regulated industries often operate within a network structure heavily influenced by regulatory requirements. Often, such contexts create rigid networks with a strong emphasis on compliance, safety, and quality control [ 86 ]. Examples include companies operating in the food and beverage, pharmaceuticals, and healthcare sectors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizations in highly regulated industries often operate within a network structure heavily influenced by regulatory requirements. Often, such contexts create rigid networks with a strong emphasis on compliance, safety, and quality control [ 86 ]. Examples include companies operating in the food and beverage, pharmaceuticals, and healthcare sectors.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, different network structures can be more (or less) favorable depending on the industry. For example, pharmaceutical supply chains may prioritize a structure that allows for higher stability and reliability over flexibility, reflecting the critical nature of pharmaceutical products and the industry's emphasis on patient safety and adherence to stringent regulations [ 86 ]. In contrast, the apparel industry is characterized by more adaptable networks oriented towards rapid response and innovation.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, our study proposes the importance of NBAs in supporting the growth of SNVs. Recent literature has highlighted how NBAs may play a role for companies (Runfola et al , 2021a). The new ventures’ need to demonstrate their sustainable impact in any activity (Ribeiro-Soriano and Piñeiro-Chousa, 2021) reinforces NBAs’ importance.…”
Section: Discussion and Theoretical Implicationsmentioning
confidence: 99%
“…La Rocca and Snehota (2021) focus on the specific role of suppliers, arguing that the new venture must select suppliers, but suppliers must also conceive it as attractive for their business. Therefore, beyond business relationships, the role of nonbusiness actors also acquires centrality in developing the new venture (Runfola et al , 2021a). Moreover, the potential networks to which the new venture can refer extend to include communities of enthusiasts concerning some passions (Pagano et al , 2018; Ranfagni and Runfola, 2018; Pagano et al , 2021) rather than new resource collection mechanisms such as crowdfunding platforms (Fortezza et al , 2021).…”
Section: Market As Network Approach and Sustainable New Ventures: A M...mentioning
confidence: 99%
“…The pandemic had a significant impact on the pharmaceutical industry, as well as other industries (Ayati, 2020). There are a significant number of global studies contributing to the area of the pharma sector, like Runfola et al (2021) emphasizing the importance of market access in the management and marketing of pharmaceutical companies; He et al (2020) conducted an event-based study on different Chinese industries and found health care industry to be resilient during the pandemic; Tirivangani et al (2021) examined the effect of COVID-19 on the pharmaceutical system and supply network in Namibia. In the Indian context, Ahmed et al (2020) reviewed the trade issues faced by Indian pharma firms in the view of current export policy intervention.…”
Section: Significance Of the Studymentioning
confidence: 99%